Early childhood education language environments: considerations for research and practice - Finders, Jennifer; Wilson, Ella; Duncan, Robert (Frontiers in Psychology, 2023)
The importance of developing early language and literacy skills is acknowledged by the United Nations Educational, Scientific, and Cultural Organization (UNESCO) as a global human rights issue (Jemeli & Fakandu, 2019). Indeed, research suggests that language abilities are foundational for a host of cognitive, behavioral, and social-emotional outcomes. Therefore, it is critical to provide experiences that foster language acquisition across early learning settings.Central to these efforts is incorporating assessments of language environments into research and practice to drive quality improvement. Yet, several barriers may be preventing language environment assessments from becoming widely integrated into early education. In this brief, we review evidence on the types of experiences that promote language development, describe characteristics of language environment assessments, and outline practical and philosophical considerations to assist with decision-making. Further, we offer recommendations for future research that may contribute knowledge regarding strategies to assess and support language development. In addressing both areas, we highlight the potential for early childhood language environments to advance equity.